Side Stream Cigarette Smoke and Its Role in Inducing Oxidative Stress in Rat Cerebral Tissue - Farindra, Irmawan; Rakhmawati, Annisa; Rusdi, Warda Elmaida; Benge, Wilhemus Dionysius Mario Randy; Farmananda, Irsandi Rizki; Rusdi, Muhammad Salsabeela (Biomedical Journal of Indonesia, 2025)
Introduction. Smoking behavior can affect not only the individual smoker but also those around them. Individuals exposed to secondhand smoke are at risk of developing similar health problems as those faced by individuals who actively smoke. Secondhand smoke causes an imbalance of systemic oxidants and antioxidants characterized by the presence of a lipid peroxidation product, namely Malondialdehyde (MDA). The main objective of this study was to assess how exposure to sidestream cigarette smoke affects MDA levels in rat cerebral tissue Methods. A true experimental study was conducted using 30 male Wistar rats with a post-test only control group design. All rats were randomly divided into 5 groups, namely 1 control group and 4 treatment groups. A total of 270 cigarettes were used as exposure sources. A spectrophotometer at a wavelength (λmax) of 533 nm was used to measure MDA levels. The MDA level data were then analyzed. ANOVA and Kruskall Wallis tests were performed after evaluating the results of the Normality and Homogeneity tests. A p value <0.05 indicates significant data. Results. The results indicate that the group exposed to cigarette smoke using 4 cigarettes for 30 days (P4) exhibited elevated MDA levels compared to the control group. Statistical analysis showed a significant correlation between secondhand smoke and increased MDA levels (p < 0.05). Conclusion. This study results suggest that exposure to SSCS contributes to increased MDA levels in the brain tissue of Wistar rats, which indicates oxidative stress.